Analysis of Teachers' Ability in Applying Science Learning Based on Religious Characters at SD Muhammadiyah 1 Karawang - Zulfa Dewina; Septi Fitri Meilana (Budapest International Research and Critics University, 2022)
The application of religious character education in a learning process is a must for teachers. Aims to build good values, especially on the value of religious character. The ability of teachers to apply science learning based on a religious character. The method used is a qualitative descriptive method using instruments of observation, interviews, and questionnaires on the religious character of students. The stages of this Research Method This research uses a qualitative descriptive approach. Based on the results of the study, it can be concluded that the teacher's ability in implementing religious character-based science learning at SD Muhammadiyah 1 Karawang is very good. Where all the teachers studied have been able to bring up religious character values. As for suggestions to related parties, both principals and the ministry of education in order to provide training for teachers to be able to develop learning oriented to the cultivation of student character values so that teachers can easily implement them in the classroom.